Strategi Pendidikan Kristen dalam Pembentukan Warga Gereja yang Unggul dan Berkarakter Berdasarkan Perspektif Kristiani - Kalis Stevanus; Nathanail Sitepu (SANCTUM DOMINE: JURNAL TEOLOGI, 2020)
Character education is an urgent need for quality Indonesian human development. Character education, apart from taking place in the context of the family and school, also takes place in the church environment. The purpose of this paper is to explain the significance of the church's strategic role as an educational agent and facilitator in shaping church members with Christ's character. The research method used is qualitative research with theological studies using the Bible and literature according to the subject, then analyzed and presented descriptively. From this research, it can be concluded that there are two strategies of the church in forming young generations with Christian characteristics, namely (1) the church must complete its wages, especially families so that the family functions as a place where Christian character and values ​​live, grow and develop in children. ; (2) the church must equip its members who are teachers so that they are committed to Christ's call for the development of teacher professionalism.